2020
DOI: 10.1002/qj.3720
|View full text |Cite
|
Sign up to set email alerts
|

What can we learn about orographic drag parametrisation from high‐resolution models? A case study over the Rocky Mountains

Abstract: Comprehensive high‐resolution numerical weather prediction models provide a virtual laboratory for modelling the atmospheric flow over complex mountain ranges. In this study, global and regional simulations with horizontal grid spacing ranging from 2 to 32 km, focused over the northern Rocky Mountains, are used to assess the orographic blocking and gravity wave drag parametrisations employed in the Met Office Unified Model (UM) and the European Centre for Medium‐Range Weather Forecasts Integrated Forecasting S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 44 publications
3
35
2
Order By: Relevance
“…This is compensated by the IFS having slightly more parametrized gravity wave drag over this region. This is opposite to what was found in Vosper et al (2019) is much weaker than that of the resolved gravity wave drag (Figure 7(c)) in most of the models. The IFS's parametrized gravity wave drag is almost identical in LR and MR.…”
Section: Gravity Wave Drag Profilescontrasting
confidence: 99%
See 2 more Smart Citations
“…This is compensated by the IFS having slightly more parametrized gravity wave drag over this region. This is opposite to what was found in Vosper et al (2019) is much weaker than that of the resolved gravity wave drag (Figure 7(c)) in most of the models. The IFS's parametrized gravity wave drag is almost identical in LR and MR.…”
Section: Gravity Wave Drag Profilescontrasting
confidence: 99%
“…In parallel, a series of studies revealed that inter-model differences in drag partitioning between different processes (partly the result of repeated tuning exercises) significantly affects the large-scale circulation over the NH (Sandu et al, 2016;Pithan et al, 2016) and the circulation response to climate change (van Niekerk et al, 2017). Further work also showed that, for at least a couple of models, the change in resolved orographic drag is not accurately balanced by the change in parametrized orographic drag when horizontal resolution is varied (van Niekerk et al, 2016;Vosper et al, 2016;Sandu et al, 2019;Vosper et al, 2019). This is a key requirement for ensuring that circulation remains robust across resolutions, so that a model can be used seamlessly for a range of applications.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Without good observations of the drag resulting explicitly from orography (rather than the combined effect of orography and the land surface within the mountainous region), it is difficult to evaluate the stress from the OGWD scheme independently. There are ongoing efforts to use high-resolution simulations (e.g., Vosper et al, 2019); however, in this study the development work on the OGWD scheme focuses largely on the model's orography ancillary and subgrid orography fields. Whilst details of orography may be thought to be well known, and hence the impact of changes small, a considerable amount of subjective processing is involved, some of which has a significant impact on the magnitude of the mean and subgrid orographic fields and, as a result, on the circulation.…”
Section: Orographic Gwd Developmentsmentioning
confidence: 99%
“…However, as more of the orography becomes explicitly resolved, the amount of (excessive) drag being applied by the subgrid OGWD scheme is reduced and the overall parametrized drag is lowered. Previous studies (e.g., van Niekerk et al, 2016;Vosper et al, 2019) have also shown that the resolution dependence of the scheme (i.e., the extent to which it transitions from subgrid to resolved orography as resolution increases) is suboptimal, and in the longer term the scheme needs to be revised to address this. Differences in the source datasets used by ECMWF and the Met Office also reveal some significant differences, particularly over Greenland and Antarctica, giving further evidence that the polar high pressure may be related to this.…”
Section: Orographic Gwd Developmentsmentioning
confidence: 99%